Development and validation of a novel microfluidic device for the manipulation of skeletal muscle microvascular blood flow in vivo. (17th April 2021) - Russell McEvoy, Gaylene M.; Shogan, Hamza; Sové, Richard J.; Fraser, Graham M.
Abstract: Objective: To develop and validate a novel liquid microfluidic approach to deliver drugs to microscale regions of tissue while simultaneously allowing for visualization and quantification of microvascular blood flow. Methods: Microfluidic devices were fabricated using soft lithographic techniques, molded in polydimethylsiloxane, and bound to a coverslip with a 600 × 300 μm micro‐outlet. Sprague‐Dawley rats, anesthetized with pentobarbital, were instrumented to monitor systemic parameters. The extensor digitorum longus muscle was dissected, externalized, and reflected across the device mounted on the stage of an inverted microscope. Doses (10 −8 to 10 −3 M) of adenosine triphosphate (ATP), acetylcholine, and phenylephrine (PE) were administered to the muscle via perfusion through the device. Microvascular blood flow directly overlying the micro‐outlet was recorded at multiple focal depths. Red blood cell (RBC) velocity, supply rate, and hematocrit were measured from recordings. Results: ATP significantly increased RBC velocity and supply rate. Increasing concentrations of PE caused a decrease in RBC velocity and supply rate. Perfusion changes were restricted to areas directly overlying the micro‐outlet and within 500 μm. Conclusions: This novel microfluidic device allows for a controlled delivery of dissolved substances to constrained regions of microvasculature while simultaneously allowing for visualization and measurement of blood flow within discrete vessels and networks.